2023
DOI: 10.1007/s10311-023-01567-5
|View full text |Cite
|
Sign up to set email alerts
|

Plants emit sulfate-, phosphate- and metal-containing nanoparticles

Abstract: As an important part of nature, the role of plants in the material cycle has been widely studied. Nanoparticles, as a common form of existence, have also been con rmed to be absorbed and retained by plants, but there are few studies on the environmental effects of exhaled nanoparticles from plants. In this paper, a sampling device is designed to sample the exhaled substances from plants in Fogang, Qingyuan, Guangdong province and Liushutang, Hunan Province, and analyzed by transmission electron microscopy. It … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
0
0
Order By: Relevance
“…During the periods of leaf development and expansion, leaves could emit methanol in the range from 10.0 to 26.8 µg g −1 [38]. Zhang et al [39] also found that the leaves of four plants could emit a great amount of nanoparticles with sizes ranging from 50 to 300 nm, which are composed of sulfate, phosphate, and metals. In contrast, few studies illustrated that inorganic carbon (e.g., BC) could be emitted from the leaves of plants to date.…”
Section: Introductionmentioning
confidence: 99%
“…During the periods of leaf development and expansion, leaves could emit methanol in the range from 10.0 to 26.8 µg g −1 [38]. Zhang et al [39] also found that the leaves of four plants could emit a great amount of nanoparticles with sizes ranging from 50 to 300 nm, which are composed of sulfate, phosphate, and metals. In contrast, few studies illustrated that inorganic carbon (e.g., BC) could be emitted from the leaves of plants to date.…”
Section: Introductionmentioning
confidence: 99%